Evolution of digital payments: Early learnings from Singapore’s cashless payment drive - NG, Dennis (Institutional Knowledge at Singapore Management University, 2018)
This paper discusses the digital payment scenario unfolding in Singapore as the country’s government ponders the tremendous leap made by China in the digital payment space. The paper discusses possible key factors contributing to the success of digital payments in China, such as the success of WeChat, and whether this could be replicated in a country like Singapore. Although China and Singapore are vastly different in size, they share many similarities, including a strong one-party government which is actively involved in the direction and growth of the economy. Both countries share similar cultural and social influences including materialism, IT adoption and an emphasis on education. This paper focuses on small-value payments, which often represent the last mile in the evolution towards a fully cashless society. Using a comparison between China and Singapore, the paper considers those factors critical for the adoption of cashless payments, such as merchant discount rates, critical mass, point-of-sale interfaces, mass transit cards, consumer behaviour and government policies.